Censorship, Speakability and Contemporary Green Fiction Cinema - Aveyard, Karina (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This article considers the relative paucity of environmental fiction films in relation to documentaries with similar thematic concerns. It engages theories of censorship, in particular, the processes of informal and prior censorship, to better understand the myriad of forces that shape the possibilities, parameters and limitations for contemporary environmentally focused cinematic narratives. It is argued that while informal modes of censorship can be difficult to discern in their everyday operation, the effects can be highly significant, influencing not only content but also form and genre.